2016
DOI: 10.1682/jrrd.2015.05.0084
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of mobility scooter-related research studies

Abstract: Abstract-Mobility scooters are three-or four-wheeled power mobility devices regularly used by people who have difficulty ambulating. They also differ from power wheelchairs in terms of their driving controls, programmability, seating, and mounting method. Given their growing popularity and anecdotal concerns around their use, a scoping review was undertaken to identify empirical research about mobility scooters and to analyze their study design and purpose. Data sources included MedLINE, Cumulative Index to Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
(85 reference statements)
1
9
0
Order By: Relevance
“…Our results show that scooter use decreases with increased age, which is in line with other studies [24,34,44]. The result probably mirrors the fact that the activity level in general decreases with increasing age [51,52].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results show that scooter use decreases with increased age, which is in line with other studies [24,34,44]. The result probably mirrors the fact that the activity level in general decreases with increasing age [51,52].…”
Section: Discussionsupporting
confidence: 93%
“…Feeling unsafe when using the scooter may also explain why 13.8% of the participants reported to use the scooter only several times a month, more seldom or never, but more studies on the feeling of safety/insecurity and its impact on scooter use are required. The issue of safety is of considerable importance, as scooter accidents seem to be rather high ranging from 1.54 to 15 per person per year [44]. In addition, in the process of constructing the QUEST 2.0 instrument, 92% of international experts rated safety as a very important item [45] underpinning that safety must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…In a scoping review conducted by Mortenson and Kim [17], two small scale, randomized control trials (RCTs) were identified. One trial found that 3D virtual reality training in combination with conventional training produced similar improvements in scooter skills as conventional training alone.…”
Section: Introductionmentioning
confidence: 99%
“…The second study found that scooter skills improved significantly with meta-cognitive training combined with on-road driving practice, compared to computerized cognitive training alone [18]. However, the validity of these findings are threatened by their small sample sizes, lack of non-intervention control arms, and use of non-validated outcome measures [17], such as the study-specific functional evaluation rating scale used in the study by Jannink et al [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Human factors are important to study because PMD drivers are a multifaceted subgroup of VRUs, which may contribute to an increased complexity in injury prevention strategies. Previous research has highlighted the importance of proper training in managing the PMD (Cassell and Clapperton 2006;Cordes et al 2018;Jancey et al 2013;Jannink et al 2008;Mortenson and Kim 2016;Mortenson et al 2017;Murphy et al 2014;Nitz 2008;Opalek et al 2009;Toosizadeh et al 2014). Because many PMD drivers experience difficulties maintaining an upright seated posture when subjected to external forces, seat belts and leg rests have been strongly recommended (Cooper et al 1998;Corfman et al 2003).…”
Section: Discussionmentioning
confidence: 99%